Examination of impulse breakdown voltage of a new EFB insulation paper - Ja’afar Adnan; Mohd Taufiq Ishak; Nurul ‘Izzati Hashim; Fakroul Ridzuan Hashim; Muhammad Aiman Amran (Penerbit Universiti Kebangsaan Malaysia, 2021)
Demand of softwood fiber has rapidly increased as a result from the variety of new softwood products. Therefore, nonwood fibers have been introduced as alternatives in pulp for presspaper making to supplement the limited wood fiber resources. Malaysia is the second largest producer of oil palm where the empty fruit bunch (EFB) has a potential to be developed as an insulating paper. This paper aims to determine the performance of EFB as non-wood fiber to evaluate its use as potential presspaper insulation in power transformer. The sample of EFB paper was produced through kraft pulping and laboratory handsheet process. The performance of EFB and kraft paper was evaluated by impulse breakdown test. The study is focused on the performance of insulating paper that were aged with the transformer oil at 90 °C for 30 days. In order to investigate the impulse breakdown voltage of the insulating paper, multistage impulse generator was used. As the aging temperature increases, the breakdown voltage will decrease. The thickness of insulating paper also has an effect to the breakdown strength as the thicker the insulating paper, the higher the breakdown voltage will be. For no aging sample, kraft fibres dominate the breakdown strength at 28.11 kV/mm, while for sample aged at 90 °C, EFB fibres dominate the breakdown strength at 3.62 kV/mm higher than the average of kraft fibres due to an effect of fibres arrangement between fibre-to-fibre bonding after the aging.